Pain satisfaction, with quality of pain management and depressive syptoms in elderly hospitalized patients - Raftopoulos, Vasilios (My University, 2005)
Objective: Our aim was to develop and test the psychometric properties of a leassessing elderly patients’ satisfaction with quality of pain management and to explore whether elderly patients’ depression (by using Geriatric Depression Scale) correlates with patients’ perceived quality of pain management.
Keywords: Satisfaction with pain management; Pain; Pain management; Depression; Quality of care; Patient satisfaction; Elderly Care; Elderly